Corporate Governance dan Kinerja Keuangan pada BUMN yang terdaftar di BEI - Nur Hidayah Al Amin; Samsul Rosadi (UIN Raden Mas Said Surakarta, 2018)
This study aims to examine the effect of Corporate Governance on financial performance by state-owned companies listed on the Indonesia Stock Exchange in 2014-2017. The aspects of Corporate Governance in this study are represented by the size of the board of commissioners, the proportion of independent commissioners, board of commissioners meetings, the size of the board of directors, and board of directors meetings. The results of the F test show that all independent variables simultaneously influence financial performance. Based on the results of the t test it can be concluded that the size of the board of commissioners has a negative effect on financial performance. The number of board meetings is reported to have a positive effect on financial performance. While the board of commissioners meeting, the size of the board of commissioners has no effect on financial performance. Keywords: board of commissioners size, board of commissioners meeting, board size, board meeting, financial performance